Effect of Chemical Compositions of Seedling Media Prepared by Spent Mushroom Compost on Seedling Growth and Development of Kale and Broccoli - PEKSEN, AYSUN; UZUN, SEZGIN (Asian Journal of Chemistry, 2010)
The objective of this research was to determine the effect of chemical composition of seedling media prepared by spent mushroom compost on seedling growth and development of kale and broccoli. Spent mushroom compost (SMC), which was kept for 18 months in open field, conventional seedling medium (CSM) consisting of a mixture of decomposed farmyard manure, sand and garden soil at a rate of 2:1:1, commercial peat (P), SMC + CSM (1:1, v/v) and SMC + P (1:1, v/v) were used. Seeds of broccoli (Brassica oleracea L. var. italica L. cv. Greenpeace F1) and kale (Brassica oleraceae L. var. acephale D.C. cv. Temel) were used. Some chemical and physical properties of different seedling media prepared by SMC were compared and their effects on days to emergence (DE), emergence percentage (EP), seedling height (SH), mean leaf area per seedling (LA) and total dry weight of seedling (DW) were determined. Correlation analyses were carried out to determine the relationships between chemical constituents of the seedling media and DE, EP, SH, LA and DW. The results revealed that SMC + P or SMC could be used as seedling media for both kale and broccoli.